Perlindungan Hukum Bagi Kreditur dalam Perjanjian Kredit dengan Jaminan Hak Tanggungan Sertifikat Tanah - Diki Andriano; Gufran; Didik Irwansah (Jurnal Hukum Lex Generalis, 2025)
Credit agreements secured by land certificate mortgage rights are key legal instruments in financial lending. In practice, legal protection for creditors often faces obstacles such as land disputes and enforcement delays. This study reveals that although creditors are legally protected under the Mortgage Law, its implementation remains suboptimal. It concludes that legal protection for creditors must be reinforced through administrative certainty in land registration and more effective mortgage enforcement mechanisms.